2021
DOI: 10.1002/hsr2.219
|View full text |Cite
|
Sign up to set email alerts
|

How to prevent ROP in preterm infants in Indonesia?

Abstract: Background and Aims Retinopathy of prematurity (ROP) is a severe disease in preterm infants. It is seen more frequently in Low‐Middle Income Countries (LMIC) like Indonesia compared to High‐Income Countries (HIC). Risk factors for ROP development are ‐extreme‐ preterm birth, use of oxygen, neonatal infections, respiratory problems, inadequate nutrition, and blood and exchange transfusions. In this paper, we give an overview of steps that can be taken in LMIC to prevent ROP and provide guidelines for screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…The differences may be associated with population and regional differences or with variations in sample size and research methods. Oxygen exposure, low birth weight, low gestational age, and breathing problems are risk factors for ROP ( 25 , 26 ). Some studies found that babies conceived by ART were more prone to developing ROP than babies conceived naturally, which seemed to be more severe.…”
Section: Discussionmentioning
confidence: 99%
“…The differences may be associated with population and regional differences or with variations in sample size and research methods. Oxygen exposure, low birth weight, low gestational age, and breathing problems are risk factors for ROP ( 25 , 26 ). Some studies found that babies conceived by ART were more prone to developing ROP than babies conceived naturally, which seemed to be more severe.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review was carried out during the development of four guidelines 10,25,32,36 (1 LMIC, 2 UMICs, 1 HIC), and was possibly used in developing the Philippine (PAO) guidelines (LMIC). Six documents 29,30,33,37,38,45 used data from national registries or national studies. In ten documents, expert consensus formed the basis of one or more components of the recommendations (4 LMICs, 1 UMIC, 5 HICs).…”
Section: Quality Of the Evidencementioning
confidence: 99%
“…25,26,29,31,33,35,37,40,41,[43][44][45][46] In these 13 guidelines and in four further documents, a paediatrician or neonatologist could initiate screening if they considered a newborn to be at risk of ROP if they fell outside the GA and BW criteria. 30,32,36,39 In five countries, 27,28,34,38,42 all indications for screening were clearly defined. The most frequently mentioned risk factors were:…”
Section: Quality Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring these risk factors will help to identify the infants who require regular screening to follow the progression of ROP and those who need treatment. It will help identify those infants who need a transfer to a center where trained ophthalmologists are available [9,10]. In this paper, we present two models to detect infants at risk to develop Type 1 ROP.…”
Section: Introductionmentioning
confidence: 99%